Deadfall [videorecording (DVD)] - Ruzowitzky, Stefan; Kristofferson, Kris; Spacek, Sissy; Bana, Eric; Wilde, Olivia; Hunnam, Charlie, 1980- (Magnolia Home Entertainment, 2013)
Siblings Addison and Liza are on the run from a casino heist gone wrong. They split up and make a run for the Canadian border in blizzard conditions, vowing to reunite in Canada. Addison heads cross-country, creating mayhem, Liza is picked up by ex-boxer Jay en-route for a Thanksgiving homecoming with his parents, and retired sheriff. It's there the siblings are reunited in a tense and thrilling showdown.